Fully digital fabrication of an occlusal device using an intraoral scanner and 3D printing: a dental technique - Waldecker, Moritz; Leckel, Michael; Rammelsberg, Peter; Bömicke, Wolfgang (The journal of prosthetic dentistry, 2019)
This dental technique describes a fully digital method for fabricating occlusal devices using a complete-arch intraoral scan and 3D printing. The maxillary and mandibular arches of a healthy, fully dentate volunteer were digitized using an intraoral scanner. A second scan and modified recording of the centric relation enabled a virtual arrangement of the maxillary and mandibular arches, both in centric relation and in the desired vertical dimension of occlusion. An occlusal device was subsequently designed virtually and fabricated from a light-polymerizing acrylic resin using a 3D printer. The occlusal device was tested for fit, occlusion, and patient-friendly handling. As only minor occlusal corrections were required, the fully digital procedure described is suitable for the fabrication of occlusal devices.